Design of Fuzzy Optimized Controller for Satellite Attitude Control by Two State actuator to reduce Limit Cycle based on Takagi-Sugeno Method - Sobutyeh Rezanezhad (Institute of Advanced Engineering and Science, 2014)
In this paper, an algorithm was presented to control the satellite attitude in orbit in order to reduce the fuel consumption and increase longevity of satellite. Because of proper operation and simplicity, fuzzy controller was used to save fuel and analyze the uncertainty and nonlinearities of satellite control system. The presented control algorithm has a high level of reliability facing unwanted disturbances considering the satellite limitations. The controller was designed based on Takagi-Sugeno satellite dynamic model, a powerful tool for modeling nonlinear systems. Inherent chattering related to on-off controller produces limit cycles with low frequency amplitude. This increases the system error and maximizes the satellite fuel consumption. Particle Swarm Optimization (PSO) algorithm was used to minimize the system error. The satellite simulation results show the high performance of fuzzy on-off controller with the presented algorithm.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5831